TEMPERATURE AND PRECIPITATION TREND IN THE ARAL SEA AND ARAL SEA REGION DURING 1960-2016 - A. Massakbayeva; J. Abuduwaili; G. T. Issanova; S. Bissenbayeva; B. Issina (Scientific Journal of Pedagogy and Economics, 2019)
Climate change in the Aral Sea and Pre-Aral region is a complex combination of global, regional, and local processes of varying spatial and temporal scales. Investigating data on temperature and precipitation in the Aral Sea and Pre-Aral region during 1960-2016, we analyzed trends using the Mann-Kendall criterion (MK). Our results showed that the maximum temperature rises by (P < 0.001) and at a speed of 1.5 ° C/decade, and the minimum temperature also rises with each decade at a speed of 6.2 °C. The Mann-Kendall static test showed that the trend of average temperatures increases by (P < 0.001) and at a speed of 3.2 °C/decade. Annual precipitation showed a significant upward trend (P < 0.001) at a rate of 0.8 mm/decade. The correlation between air temperature and precipitation was R = 0.265. It is assumed that the results of this study will contribute to a deeper understanding of climate change in the Aral Sea and Pre-Aral region.